A salvação do cosmos no Evangelho de João - Silva, José Dias da (2021)
This research investigates the “Salvation of the Cosmos in the Gospel of John” and aims to demonstrate that the community reflected in this literature has taken on as its mission the purpose of manifesting a soteriological message to the cosmos. “Cosmos” was a fundamental concept in understanding the relationship between the Johannine community and its environment. To illuminate this understanding, the phases of reconstitution of the Johannine story were verified; the interaction of this group with others in its immediate environment; the exchange of thoughts in that culture and; the mapping of the word cosmos in the Fourth Gospel. Starting from this approach, it could be discovered that “cosmos” is a polysemic concept in the Gospel of John, which can be characterized as negative, neutral and positive; that conflicts arising from relationships with other groups strongly contributed to their negative conception; that there are similarities and at the same time divergences with other cosmologies; and that the semantic field of the term cosmos in John clarifies that his community was not closed in the face of rejections, on the contrary, it assumes its task of being light where it found itself.(AU)